2023
DOI: 10.21511/imfi.20(4).2023.19
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity spillover from carbon emission trading markets to stock markets in China

Xinyuan Yang,
Jingyao Zhu,
Hantao Xie
et al.

Abstract: This study delves into China’s carbon emissions trading markets, investigating the interplay between carbon price liquidity and stock liquidity. Focusing on 338 companies listed in the national and eight pilot markets of the carbon emissions trading system from August 2013 to October 2023, the empirical finding reveals a positive impact of carbon price liquidity on stock liquidity. Notably, this positive association manifests more robustly in industries characterized by low carbon intensity compared to those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Zhang and Zhang (2023) disclosed R 2 between 0.003 and 0.009 in their analysis linking individual stock returns to carbon price returns. Likewise, Yang et al (2023) presented an adjusted R 2 of 0.037 when examining liquidity spillover from carbon to stock markets. Tian et al (2016) reported an R 2 of 0.055 in their study correlating individual stock returns with European carbon returns.…”
Section: Baseline Regressionsmentioning
confidence: 99%
“…Zhang and Zhang (2023) disclosed R 2 between 0.003 and 0.009 in their analysis linking individual stock returns to carbon price returns. Likewise, Yang et al (2023) presented an adjusted R 2 of 0.037 when examining liquidity spillover from carbon to stock markets. Tian et al (2016) reported an R 2 of 0.055 in their study correlating individual stock returns with European carbon returns.…”
Section: Baseline Regressionsmentioning
confidence: 99%
“…Using a variety of techniques, empirical research has also looked at the link between monhttp://dx.doi.org/10.21511/bbs.19 (1).2024.07 etary stability and CBI. A widely used approach is the Vector Autoregression (VAR) method (Zhuravka et al, 2023;Yang et al, 2023;Le et al, 2023;Seyfullayev, 2023). For instance, Riaz and Ramakrishnan's study examines the relationship between Pakistan's monetary stability and CBI.…”
Section: Literature Reviewmentioning
confidence: 99%